Vulnerability Analysis and Prevention on Software as a Service (SaaS) of Archive Websites - Mushlihudin Mushlihudin; Danis Faisal (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Web Archive is a SaaS service that has an important role in providing better document storage and management. Good document management has a positive impact on optimizing business operations, increasing collaboration, reducing costs, and protecting sensitive information. Cybercrime, which has an increasingly high intensity, is a serious threat to the security of data stored in web archives. This research aims to improve data security on web archives by conducting ongoing testing. Testing was carried out on a server with a Linux operating system and web archives managed by a file manager system. This study tests the attack using the OWASP application method, and an XSS attack on a web archive with a Linux server and using a file management application. The testing phase includes Information Gathering, Vulnerability Assessment, Exploiting, and Reporting. Based on the results of the research, it was obtained that the first vulnerability test contained 9 vulnerabilities in 9 categories. The second vulnerability test obtained 7 vulnerabilities and the third test found no vulnerabilities. At the end of each test, recommendations for improvements to the web archive are made to the web archive manager and a re-testing process for vulnerabilities is carried out. This process is carried out repeatedly with continuous improvement. Testing the attack and repair of the web archive was carried out repeatedly and managed to get a vulnerability level of Level 0.1-3.9 points with Low status.